Spectrophotometric flow-injection determination of sulphite in white wines involving gas diffusion through a concentric tubular membrane - Melo, Denise; Zagatto, Elias A. G.; Mattos, Ivanildo L. [UNESP]; Maniasso, Nelson (FapUNIFESP (SciELO), 2003)
A flow-injection system is proposed for the spectrophotometric determination of sulphite in white wines. The method involves analyte conversion to SO2, gas diffusion through a Teflon® semi-permeable membrane, collection into an alkaline stream (pH 8), reaction with Malachite green (MG) and monitoring at 620 nm. With a concentric tubular membrane, the system design was simplified. Influence of reagent concentrations, pH of donor and acceptor streams, temperature, timing, surfactant addition and presence of potential interfering species of the wine matrix were investigated. A pronounced (ca. 100%) enhancement in sensitivity was noted by adding cetylpyridinium chloride (CPC). The proposed system is robust and baseline drift is not observed during 4 h operating periods. Only 400 μL of sample and 0.32 mg MG are required per determination. The system handles 30 samples per hour, yielding precise results (r.s.d. < 0.015 for 1.0 - 20.0 mg L-1 SO2) in agreement with those obtained by an alternative procedure.
Keywords: Concentric tubular membrane; Gas diffusion; Micellar medium; Spectrophotometric flow analysis; Sulfite; cetylpyridinium salt; malachite green; reagent; sulfite; surfactant; alkalinity; flow injection analysis; gas diffusion; membrane; membrane permeability; pH; spectrophotometry; temperature; wine